Psychology of health and fitness - Brehm, Barbara A. (F.A. Davis Company, 2014)
Apply the science of health and fitness psychology to yourpractice! Learn how to apply the psychology of health and fitness to your exercise programs and to solve themotivational and behavioral problems you.ll encounter every day in practice. You.ll explore the scientific principles and variables that influence behavior as you develop the confidence to design effective lifestyle interventions for disease prevention and develop individualized exercise programs that promote optimal health.--Publisher
Keywords: Behavior modification; Clinical health psychology; Health attitudes; Health Behavior; Physical fitness -- Psychological aspects